ERGONOMIC USE AND SHAPE OF MOBILE PHONES TO AVOID WORK ACCIDENTS - Gempur Santoso (Bajang Institute, 2024)
The main use of Android mobile phones is for massive communication. However, there are still many incidents of complaints and accidents due to the use of cellphones. This article aims to reveal the ergonomic use and shape of mobile phones to avoid work accidents. This article is planned descriptively, meaning that the data is analyzed and then presented. Data is taken from various research opinions or what is usually called literature studies. The analysis was also carried out descriptively. Conclusion: 1). The impacts of using mobile phones include: when driving there is a tendency for accidents, addiction, emotional disorders, social behavior disorders, attention deficit disorders, pain and tension in the neck muscles. Therefore, there needs to be a threshold for the length of time you use a cell phone, driving speed when using a cell phone, when communicating using the five senses, please do not use a cell phone at the same time, and when using a cell phone, don't bend over. 2). The ergonomic shape of the mobile phone takes into account: the size of the mobile phone is wide and thick according to the anthropometry of the length of the middle finger and the length of the thumb, and the length of the mobile phone matches the length between the ear and the mouth. Then, from an ergonomic perspective, you also pay attention to the shape, weight, and materials used in the mobile phone body. From an ergonomic perspective, mobile phones can be operated with one hand, the buttons are easy to reach, responsive and comfortable. Suggestion: Cell phone users should choose a cell phone that is ergonomic in terms of size, shape, weight, material and the buttons are easy to reach, so it is safe and avoids work accidents.